Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Sure, let's break down the steps to solve this problem.
### Step 1: Find the Center of the Given Circle
First, let's work on the given equation of the circle:
[tex]\[ x^2 + y^2 - 8x - 6y + 24 = 0 \][/tex]
To identify the center, we'll complete the square for \(x\) and \(y\).
#### Completing the Square for \(x\):
1. Extract the \(x\) terms:
[tex]\[ x^2 - 8x \][/tex]
2. Complete the square:
Add and subtract \((\frac{8}{2})^2 = 16\):
[tex]\[ x^2 - 8x + 16 - 16 \][/tex]
This simplifies to:
[tex]\[ (x - 4)^2 - 16 \][/tex]
#### Completing the Square for \(y\):
1. Extract the \(y\) terms:
[tex]\[ y^2 - 6y \][/tex]
2. Complete the square:
Add and subtract \((\frac{6}{2})^2 = 9\):
[tex]\[ y^2 - 6y + 9 - 9 \][/tex]
This simplifies to:
[tex]\[ (y - 3)^2 - 9 \][/tex]
#### Combining everything:
So, the given equation becomes:
[tex]\[ (x - 4)^2 - 16 + (y - 3)^2 - 9 + 24 = 0 \][/tex]
Simplify this:
[tex]\[ (x - 4)^2 + (y - 3)^2 - 1 = 0 \][/tex]
Thus,
[tex]\[ (x - 4)^2 + (y - 3)^2 = 1 \][/tex]
From this equation, we can see that the center \((h, k)\) of the original circle is \((4, 3)\).
### Step 2: Form the Equation for the New Circle
The problem states that the new circle has a radius of 2 units and the same center as the original circle \((4, 3)\).
The general form of a circle's equation is \((x - h)^2 + (y - k)^2 = r^2\).
Substituting in the values:
- Center \((h, k) = (4, 3)\)
- Radius \(r = 2\)
The equation becomes:
[tex]\[ (x - 4)^2 + (y - 3)^2 = 2^2 \][/tex]
### Step 3: Compare with the Given Choices
We need to match \((x - 4)^2 + (y - 3)^2 = 2^2\) with one of the provided options:
- \((x+4)^2+(y+3)^2=2\)
- \((x-4)^2+(y-3)^2=2\)
- \((x-4)^2+(y-3)^2=2^2\)
- \((x+4)^2+(y+3)^2=2^2\)
### Step 4: Verify the Correct Choice
The correct choice is the one that matches our derived equation \((x - 4)^2 + (y - 3)^2 = 2^2\):
Therefore, the correct option is:
[tex]\[ (x - 4)^2 + (y - 3)^2 = 2^2 \][/tex]
Hence, the equation representing the new circle is:
[tex]\[ \boxed{(x-4)^2 + (y-3)^2 = 2^2} \][/tex]
### Step 1: Find the Center of the Given Circle
First, let's work on the given equation of the circle:
[tex]\[ x^2 + y^2 - 8x - 6y + 24 = 0 \][/tex]
To identify the center, we'll complete the square for \(x\) and \(y\).
#### Completing the Square for \(x\):
1. Extract the \(x\) terms:
[tex]\[ x^2 - 8x \][/tex]
2. Complete the square:
Add and subtract \((\frac{8}{2})^2 = 16\):
[tex]\[ x^2 - 8x + 16 - 16 \][/tex]
This simplifies to:
[tex]\[ (x - 4)^2 - 16 \][/tex]
#### Completing the Square for \(y\):
1. Extract the \(y\) terms:
[tex]\[ y^2 - 6y \][/tex]
2. Complete the square:
Add and subtract \((\frac{6}{2})^2 = 9\):
[tex]\[ y^2 - 6y + 9 - 9 \][/tex]
This simplifies to:
[tex]\[ (y - 3)^2 - 9 \][/tex]
#### Combining everything:
So, the given equation becomes:
[tex]\[ (x - 4)^2 - 16 + (y - 3)^2 - 9 + 24 = 0 \][/tex]
Simplify this:
[tex]\[ (x - 4)^2 + (y - 3)^2 - 1 = 0 \][/tex]
Thus,
[tex]\[ (x - 4)^2 + (y - 3)^2 = 1 \][/tex]
From this equation, we can see that the center \((h, k)\) of the original circle is \((4, 3)\).
### Step 2: Form the Equation for the New Circle
The problem states that the new circle has a radius of 2 units and the same center as the original circle \((4, 3)\).
The general form of a circle's equation is \((x - h)^2 + (y - k)^2 = r^2\).
Substituting in the values:
- Center \((h, k) = (4, 3)\)
- Radius \(r = 2\)
The equation becomes:
[tex]\[ (x - 4)^2 + (y - 3)^2 = 2^2 \][/tex]
### Step 3: Compare with the Given Choices
We need to match \((x - 4)^2 + (y - 3)^2 = 2^2\) with one of the provided options:
- \((x+4)^2+(y+3)^2=2\)
- \((x-4)^2+(y-3)^2=2\)
- \((x-4)^2+(y-3)^2=2^2\)
- \((x+4)^2+(y+3)^2=2^2\)
### Step 4: Verify the Correct Choice
The correct choice is the one that matches our derived equation \((x - 4)^2 + (y - 3)^2 = 2^2\):
Therefore, the correct option is:
[tex]\[ (x - 4)^2 + (y - 3)^2 = 2^2 \][/tex]
Hence, the equation representing the new circle is:
[tex]\[ \boxed{(x-4)^2 + (y-3)^2 = 2^2} \][/tex]
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.